2023
DOI: 10.3390/diagnostics13182954
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Neutrophil-to-Lymphocyte Ratio to Identify Bacterial Infection and Predict Short-Term Mortality in Patients with Acutely Decompensated Cirrhosis

Tamás Janka,
Dávid Tornai,
Mária Papp
et al.

Abstract: Liver cirrhosis patients are highly susceptible to infections, affecting survival, but current parameters for detecting infection are not reliable enough in this population. We investigated the ability of white blood cell (WBC), ∆WBC, neutrophil and ∆neutrophil counts, neutrophil-to-lymphocyte (NLR) and ∆NLR ratios and C-reactive protein (CRP) and procalcitonin (PCT) levels to identify infection and predict short-term mortality in liver cirrhosis patients. We recruited 233 patients with liver cirrhosis hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Previously, COVID-19-related studies showed that NLR was more sensitive than the absolute neutrophil, or lymphocyte count, as a marker of the SI response [20,21] Horvatits et al [22] indicate that elevated NLR is correlated with hepatic lobular injury, hepatic fibrosis, and fatty liver. Also, they concluded that immune dysfunction is connected to the high NLR.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, COVID-19-related studies showed that NLR was more sensitive than the absolute neutrophil, or lymphocyte count, as a marker of the SI response [20,21] Horvatits et al [22] indicate that elevated NLR is correlated with hepatic lobular injury, hepatic fibrosis, and fatty liver. Also, they concluded that immune dysfunction is connected to the high NLR.…”
Section: Discussionmentioning
confidence: 99%